2016
DOI: 10.18203/2320-6012.ijrms20164046
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of antihypertensive drug prescription patterns and adherence to joint national committee-8 hypertension treatment guidelines among hypertensive patients attending a tertiary care teaching hospital

Abstract: Background:The new guidelines issued by the joint national committee on prevention, detection, evaluation, and treatment of high blood pressure (JNC-8) emphasize that aggressive blood pressure (BP) control is essential to reducing morbidity and mortality. Patient non-adherence is a serious obstacle to the effective treatment of many acute and chronic disorders. Successful treatment and outcome of a chronic disease such as hypertension depend on many factors, including resources (e.g., funds, space, and people)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
13
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 16 publications
9
13
2
Order By: Relevance
“…This study also reveals that hypertension is more prevalent in elderly patients belonging to age group 40-60 or more. Study conducted by Romday et al13 and Tiwari et al19 found most Present study results fall in line of the study by Romday R et al (2016) 13. Study done by Amira et al23 and Kothari et al16 found 36.6% and 47.72% patients respectively were suffering with comorbid conditions.…”
supporting
confidence: 80%
“…This study also reveals that hypertension is more prevalent in elderly patients belonging to age group 40-60 or more. Study conducted by Romday et al13 and Tiwari et al19 found most Present study results fall in line of the study by Romday R et al (2016) 13. Study done by Amira et al23 and Kothari et al16 found 36.6% and 47.72% patients respectively were suffering with comorbid conditions.…”
supporting
confidence: 80%
“…According to (Singla et al, 2018) ARB (45.47%), BB(9.09%), CCB(22.75%), ACEI(20.64%), DI (2.05%). According to (Romday et al, 2016) DI (29.48%) is highly used but it's a contradict result to our observations. CCB (21.96%) which is next to highly used similar to our observations.…”
Section: Monotherapycontrasting
confidence: 96%
“…In our study we observed BB+ ARB are highly used it occupies 19.73% and complies with Haq et al (2019) and (Singla et al, 2018) (47.46%) but (4.81%) according to (Romday et al, 2016) entirely contradict to our observation. BB+CCB (17.27%) and in (Singla et al, 2018) (4.13%) but (Romday et al, 2016) indicates 12.04% similar to our observations. (17.12%) ARB+DI but according to (Singla et al, 2018) (24.76%) indicating next highly used combination and 21.67% indicated in (Romday et al, 2016).…”
Section: Dual Therapycontrasting
confidence: 90%
“…The study revealed that the highest number of diseases and comorbid conditions were hypertension alone were 162 (40.90%), hypertension+diabetes were 68 (17.17%), and Hypertension+ Cardiovascular diseases were 41 (10.35%), the most co-morbidities disease in hypertensive patients, and also the most of the female patients had found to be hypertensive and shown PDDIs (table 6), a similar study conducted by Romday et al (2016) [14] reported that Diabetes mellitus (9.36%, males; 8.96%, females), other cardiovascular diseases (14.05%, males; 13.43%, females), acid peptic disease (7.69%, males; 7.46%, females) and dyslipidemia (11.70%, males; 13.43%, females) are the most common comorbidities in hypertension patients.…”
Section: Discussionsupporting
confidence: 58%